FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI MADRASAH ALIYAH BAHRUL MUBARAK TORONIPA - Eriyani, Yuyun; Mochtar, Febriana; Yunawati, Irma (NHM PRESS, 2023)
Anemia is a condition where the hemoglobin level in the blood is lower than the normal value. Adolescent girls are a group at risk of anemia. This study aims to determine the factors associated with the incidence of anemia in adolescent girls at Madrasah Aliyah Bahrul Mubarak Toronipa. This type of research is quantitative research with an observational analytic method and a cross-sectional approach. This study used a total sampling technique with a sample size of 60 female students. Data analysis using univariate and bivariate analysis using the chi-square test The results showed that the incidence of anemia was 36.7%, iron intake in the deficit category was 43.3%, consumption patterns of inhibitors in the frequent category were 48.3%, and consumption patterns of enhancers in the rare category were 53.3%. The results of statistical tests using the chi-square test showed that the factors associated with the incidence of anemia were iron intake (p = 0.032), iron inhibitor consumption patterns (p = 0.009), and iron enhancer consumption patterns (p = 0.043). The conclusion in this study is that the factors associated with the incidence of anemia in adolescent girls at Madrasah Aliyah Bahrul Mubarak Toronipa are iron intake and consumption patterns of iron inhibitors and enhancers. It is recommended that the school increase the prevention of anemia by working with the Snearest health center in the form of education and giving blood supplement tablets. Respondents are expected to pay more attention to iron intake and enhancer consumption patterns and not consume inhibitor sources less than 1 hour before or after meals.